1981
DOI: 10.1364/ol.6.000111
|View full text |Cite
|
Sign up to set email alerts
|

Saturable Fabry–Perot filter for nonlinear optical image processing

Abstract: Experimental results of nonlinear optical image processing by a saturable Fabry-Perot filter are described. Fulgide, a photochromic compound, in toluene is used as a saturable absorber for the green light of an Ar-ion laser. Image thresholding using a steep increase of transmission with a critical power density of 700 mW/cm(2) is demonstrated. The spatial resolution is found to be more than 10 lines/mm over a 30-mm-diameter aperture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Photochromic materials will generally afford these effects over longer time scalesand thus build up a larger nonlinear responsethan regular, nonphotochromic species, where a short-lived excited state perturbs the absorption. Photochromic fulgides were used in early studies of saturable absorption and bistability. , …”
Section: B Third-order Nlo Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Photochromic materials will generally afford these effects over longer time scalesand thus build up a larger nonlinear responsethan regular, nonphotochromic species, where a short-lived excited state perturbs the absorption. Photochromic fulgides were used in early studies of saturable absorption and bistability. , …”
Section: B Third-order Nlo Propertiesmentioning
confidence: 99%
“…Photochromic fulgides were used in early studies of saturable absorption and bistability. 56,57 The spiropyran-merocyanine transformation has been used to demonstrate ultrafast switching resulting from the change in refractive index. 58 In this study, a right-angle prism is covered on its hypotenuse with a thin film (50 nm) of silver, and a film of spiropyran in polystyrene.…”
Section: B Third-order Nlo Propertiesmentioning
confidence: 99%
“…Mitsuhashi reported that the rapid change of transmission of 4 in the visible light region by light irradiation was applied to the nonlinear, real-time optical image processing . The spatial resolution was more than 10 lines/mm over a 30 mm diameter aperture.…”
Section: F Control Of Transmittance Of Visible Lightmentioning
confidence: 99%
“…[16,17] Instead, the correlation between incident and transmitted intensities deviates from linearity when a photochromic material fills the interferometer cavity. [18][19][20] The photoinduced absorbance and refractiveindex changes associated with the photochromic transformation are responsible for the nonlinear response. For example, the irradiation of a polymethylmethacrylate film doped with the fulgide 3 at 366 nm causes the appearance of a band in the visible region of the absorption spectrum (a and b in Figure 4) and a concomitant increases in refractive index (c).…”
Section: Introductionmentioning
confidence: 99%